On ramped vanes to control normal shock boundary layer interactions. (17th September 2018) - Lee, S.; Loth, E.
ABSTRACT: A novel vortex generator design positioned upstream of a normal shock followed by a subsequent diffuser was investigated using large eddy simulations. In particular, "ramped-vane" flow control devices with three different heights relative to the incoming boundary layer thickness (0.34δ, 0.52δ and 0·75δ) were placed in a supersonic boundary layer with a freestream Mach number of 1.3 and a Reynolds number of 2400 based on the momentum thickness. This is the first numerical study to investigate the size effect of the ramped-vane for flow control device in terms of shape factor, flow separation and flow unsteadiness. The results showed that these devices generated strong streamwise vortices that entrained high-momentum fluid to the near-wall region and increased turbulent mixing. The devices also decreased shock-induced flow separation, which resulted in a higher downstream skin friction in the diffuser. In general, the largest ramped-vane (0.75δ) produced the largest reductions in flow separation, shape factor and overall unsteadiness. These results and a careful review of the literature study also determined the quantitative correlation of optimum VG height with Mach number, whereby h /δ 1 is often optimum for incompressible flows while higher Mach numbers lead to small optimum heights, tending towards h/δ 0.45 at M =2.5.